* Answer

* Discussion

* Share

It is known that,

Question 2:

* Answer

* Discussion

* Share

It is known that,

Question 3:

* Answer

* Discussion

* Share

It is known that,

Question 4:

* Answer

* Discussion

* Share

It is known that,

From equations (2) and (3), we obtain

Question 5:

* Answer

* Discussion

* Share

It is known that,

Question 6:

* Answer

* Discussion

* Share

It is known that,

Question 1:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 2:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 3:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 4:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 5:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 6:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 7:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 8:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

uestion 9:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

uestion 10:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 11:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 12:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 13:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 14:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 15:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 16:

* Answer

* Discussion

* Share

Let

Equating the coefficients of x and constant term, we obtain A = 10 and B = −25

Substituting the value of I1 in (1), we obtain

Question 17:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 18:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

stion 19:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 20:

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Question 21:

equals

A.

B.

C.

D.

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Hence, the correct answer is D.

Question 22:

equals

A.

B.

C.

D.

* Answer

* Discussion

* Share

By second fundamental theorem of calculus, we obtain

Hence, the correct answer is C.

Question 1:

* Answer

* Discussion

* Share

When x = 0, t = 1 and when x = 1, t = 2

Question 2:

* Answer

* Discussion

* Share

Also, let

Question 3:

* Answer

* Discussion

* Share

Also, let x = tanθ ⇒ dx = sec2θ dθ

When x = 0, θ = 0 and when x = 1,

Takingθas first function and sec2θ as second function and integrating by parts, we obtain

Question 4:

* Answer

* Discussion

* Share

Let x + 2 = t2 ⇒ dx = 2tdt

When x = 0, and when x = 2, t = 2

Question 5:

* Answer

* Discussion

* Share

Let cos x = t ⇒ −sinx dx = dt

When x = 0, t = 1 and when

Question 6:

* Answer

* Discussion

* Share

Let ⇒ dx = dt

Question 7:...

## Share this Document

Let your classmates know about this document and more at StudyMode.com